Simultaneous HPLC method development and validation of moxifloxacin hydrochloride and bromofenac sodium in pharmaceutical formulation - Shine Sudev; Vishnumanikandan N; Sapna Shrikumar; Ajmal Shareef K; Najuma salim (International Journal of Pharmacy and Analytical Research, 2015)
This paper deals with the simultaneous reversed – phase HPLC method development for the for the simultaneous determination of Moxifloxacin Hydrochloride and Bromofenac Sodium in Pharmaceutical preparation. The chromatographic separation was carried out using a STD Hyber C18 column, 150× 4.6mm i.d, 5µ particle size in isocratic mode with flow rate of 1mLmin-1 and the detection was carried out by Photo diode array detector at 280nm. The mobile phases consist of 0.01N Sodium Dihydrogen Ortho Phosphate buffer (pH 4 ±0.5) and Acetonitrile in the ratio of 65:35 (v/v). The total chromatographic analysis per sample was approximately 6 mints. Retention times for Moxifloxacin Hydrochloride and Bromofenac Sodium were found to be 2.26 and 5.72 min respectively. A linear response curve was observed over the concentration range of 25-150µgmL-1 and 4.5-27µgmL-1 for Moxifloxacin Hydrochloride and Bromofenac Sodium. The method was statistically validated as per ICH guidelines and % RSD was found to be less than 2 indicating high degree of accuracy and precision of the proposed HPLC method. Hence the proposed method can be applied for the quantitative analysis of Moxema and Bromday eye drops.